Towards Decarbonizing Concrete Industry in Egypt: Material Alternatives, and Economic Viability - Gamal, Reem (AUC Knowledge Fountain, 2026)
The construction industry remains one of the largest contributors to global greenhouse gas emissions, with cement and steel production accounting for approximately 15% of total emissions. As global infrastructure demands continue to rise, there is an increasing need for practical tools that support low-carbon construction practices in line with international climate commitments. This research presents the development and testing of a mathematical, adaptable decision support system designed to assess both the environmental and financial impacts of material selection in concrete production. Focusing on life cycle stages A1 to A3, raw material extraction, transportation, and manufacturing, the decision support system enables evaluation of various low-carbon alternatives for cement, steel, and aggregates. The decision support system is built on Microsoft Excel while featuring a user-friendly interface that allows full customization of concrete and material choices, including manufacturer selection and dosage adjustment. Drawing from a comprehensive database of certified Environmental Product Declarations (EPDs), it integrates emissions and cost data from both local and global sources, making it applicable across diverse geographic and market contexts. The decision support system is designed to support informed decision-making by balancing sustainability targets with economic feasibility. To experience its effectiveness, the decision support system was tested using a dataset of over 100 certified EPDs and applied to ten real-world construction projects in Egypt, covering a range of scales and locations. Results demonstrated that the use of low-carbon alternatives achieved an average reduction of 13% in embodied carbon, with an associated average cost increase of 33%. A local and global sensitivity analysis further tested the decision support system’s responsiveness to variations in emission factors, material availability, and market prices. Through Pareto-based analysis, the decision support system identified the finest material combinations that balance environmental performance with financial viability. By offering a scalable and technically accessible solution, this research contributes to the global decarbonization of the construction sector and supports national efforts to meet international climate targets under the Paris Agreement.